Ritual Massuro Baca Pada Masyarakat Bugis Tinco Bone Perspektif Maqashid al-Syari’ah - Budiarti Budiarti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2021)
This study aims to explore the functional relation of the meaning of massuro baca as a local wisdom of the Bugis Tinco community in Bone, South Sulawesi, from the perspective of maqashid al-syari'ah. Maqashid al-syari'ah is used as the main research approach, supported by theological, historical, and sociological normative approaches. Utilizing the techniques of observation, interviews, and documentation in data collection. The results showed that the ritual of massuro baca was an expression of the Shari'a in the cultural and customary domains identified in the social relationship category. The ritual of massuro baca in the Bugis Tinco community from the perspective of maqashid al-syari'ah is an expression of gratitude to Allah swt. on the one hand and the discursive practice of avoiding the harm of kufr. This cultural ritual has benefits for the community with the level of benefit tahsiniyat (terseier) and 'urf hasanah (good custom) because it serves to glue kinship and family solidity.